PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK PADA MATA PELAJARAN IPA KELAS III SDN 3 JUNJUNG KECAMATAN SUYMBERGEMPOL KABUPATEN TULUNGAGUNG - Evi Khoiriyah; Eka Yuliana Sari (Universitas Kanjuruhan Malang, 2018)
Learning media is the most important thing in achieving the learning objectives. But in fact the media is very rarely used in learning in the classroom. Learning in the classroom also seems monotonous because it often only utilizes images as learning media. This causes students to feel bored and lead to ineffective learning. To arouse the spirit and motivation of students in following the learning in the classroom, need a media with a fun innovation and cultivate students' curiosity is by using Pop-Up Book media. the purpose of this study is to determine the level of eligibility, stability and effectiveness of the use of Pop-Up Book media. The type of research used is research and development (R & D) with development procedures according to Sugiyono. The results showed that the level of product feasibility by material experts and media experts included in the category valid and feasible to use but needs to be revised. From the results of media tersembapan data show the results of learning media Pop-Up Book valid and feasible applied to science learning. The level of media effectiveness also shows that the students as a whole complete in the learning by looking at the average student score above the KKM that is equal to 95.3.